2011
DOI: 10.5732/cjc.010.10566
|View full text |Cite
|
Sign up to set email alerts
|

Loss of A-type lamin expression compromises nuclear envelope integrity in breast cancer

Abstract: Through advances in technology, the genetic basis of cancer has been investigated at the genomic level, and many fundamental questions have begun to be addressed. Among several key unresolved questions in cancer biology, the molecular basis for the link between nuclear deformation and malignancy has not been determined. Another hallmark of human cancer is aneuploidy; however, the causes and consequences of aneuploidy are unanswered and are hotly contested topics. We found that nuclear lamina proteins lamin A/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 42 publications
3
52
0
1
Order By: Relevance
“…In conclusion, altered lamin expression or localization and disrupted stoichiometry between A- and B-type lamins can change the elastic properties of the NE, 16 which renders it unable to withstand cytoskeleton- 47 , 48 and chromosome-based 49 , 50 forces and leads to misshapen nuclei. Consistently, downregulation of lamin A/C in non-cancer primary breast epithelial cells results in nuclear alterations similar to those observed in breast cancer cell 38 . Moreover, mutations in LMNA and other genes encoding for proteins of nuclear lamina results in heritable diseases called laminopathies, 51 which are also characterized by fragile 52 and multi-lobulated nuclear shape 53 .…”
Section: Nuclear Organization Is Disrupted In Cancer Cellssupporting
confidence: 55%
See 1 more Smart Citation
“…In conclusion, altered lamin expression or localization and disrupted stoichiometry between A- and B-type lamins can change the elastic properties of the NE, 16 which renders it unable to withstand cytoskeleton- 47 , 48 and chromosome-based 49 , 50 forces and leads to misshapen nuclei. Consistently, downregulation of lamin A/C in non-cancer primary breast epithelial cells results in nuclear alterations similar to those observed in breast cancer cell 38 . Moreover, mutations in LMNA and other genes encoding for proteins of nuclear lamina results in heritable diseases called laminopathies, 51 which are also characterized by fragile 52 and multi-lobulated nuclear shape 53 .…”
Section: Nuclear Organization Is Disrupted In Cancer Cellssupporting
confidence: 55%
“…For example, in small cell lung cancer (SCLC) cells A-type lamins are either not or only weakly expressed, while in non-SCLC cells they are normally expressed but frequently mislocalized in the cytoplasm 32 - 34 . In colon cancers, 35 gastric cancers, 36 , 37 breast cancers, 38 , 39 and diffuse large B-cell lymphomas, 40 the expression of A-type lamins is also strongly reduced, and this feature correlates with increased disease recurrence and poor patient prognosis. Consequently, the nuclei of these cancer types are often fragile and lobulated, and in breast cancer cells, they were shown to contain massive NE membrane invaginations 27 , 28 (Fig.…”
Section: Nuclear Organization Is Disrupted In Cancer Cellsmentioning
confidence: 99%
“…Loss or reduction of lamin A/C expression is often found in cancer cells [47], including leukemia [48, 49], colon [50], prostate [29], lung [51], breast [52], and gastric cancers [53, 54]. Our earlier study also found that lamin A/C expression is lost in about 60 % of serous ovarian carcinomas, in which the mRNA is often present despite the loss of protein [55].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced expression of lamin in tumor cells compared to normal has been reported by some in refs. [], whereas increased expression has been reported by others. It is clear that lamins have multiple functions, which range from providing structure to the nucleus to being associated with transmembrane proteins and regulating signaling.…”
Section: Intermediate Filamentsmentioning
confidence: 77%